2019
DOI: 10.1177/0300060518821033
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic late thrombocytosis is a common finding in very preterm infants even in the absence of erythropoietin treatment

Abstract: Objectives Thrombocytosis is more prevalent in pediatric than in adult patients and is associated with complications or worsened outcomes after vascular events. This study aimed to determine the prevalence of thrombocytosis in very preterm infants who had not received human recombinant erythropoietin treatment (rHuEPO) and its relationship with other hematological parameters and clinical complications. Methods We performed a retrospective study of hematological and clinical data of very preterm infants who wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Erythropoietin (EPO), a regulator of erythrocyte production, is structurally similar to TPO with an amino terminal domain containing a sequence homologous to that of EPO [ 17 , 18 ]. Preterm infants with thrombocytosis show decreased red blood cell counts and elevated endogenous EPO levels due to anemia, which probably results in elevated platelet counts [ 4 ]. Increased production of thrombopoietic factors, cytokines, and other hematopoietic growth factors due to anemia might be related to elevated platelet counts as well [ 2 ].…”
Section: Pathophysiologymentioning
confidence: 99%
See 3 more Smart Citations
“…Erythropoietin (EPO), a regulator of erythrocyte production, is structurally similar to TPO with an amino terminal domain containing a sequence homologous to that of EPO [ 17 , 18 ]. Preterm infants with thrombocytosis show decreased red blood cell counts and elevated endogenous EPO levels due to anemia, which probably results in elevated platelet counts [ 4 ]. Increased production of thrombopoietic factors, cytokines, and other hematopoietic growth factors due to anemia might be related to elevated platelet counts as well [ 2 ].…”
Section: Pathophysiologymentioning
confidence: 99%
“…In one study, thrombocytosis was found in 38% of low birth weight preterm infants [ 3 ]. Thrombocytosis was observed in 32.6% of preterm infants with a gestational age <32 weeks who had not received recombinant human EPO [ 4 ]. Higher TPO concentrations [ 3 , 32 ] and more sensitive megakaryocyte precursor cells [ 3 ] in preterm versus term infants are the speculated cause ( Fig.…”
Section: Thrombocytosis In Preterm Infantsmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, the relationship between platelet counts and ROP remains poorly defined. Most studies observe an association between thrombocytopenia and ROP development or severity [ 12 , 13 , 14 ], while others find no association [ 15 , 16 ]; one recent study even documented that thrombocytosis is associated with ROP [ 17 ]. These differences may be attributed to differences in study methodology and statistical analysis, as the majority of these studies evaluated platelet levels as a qualitative variable.…”
Section: Introductionmentioning
confidence: 99%